Dispersion stability and tribological characteristics of TiO2/SiO2 nanocomposite-enriched biobased lubricant - Gulzar, Muhammad; H. H., Masjuki; Kalam, M. A.; Munusamy, Mahendra Varman; Mohd Zulkifli, Nurin Wahidah; Mufti, R. A.; Zahid, R.; Yunus, R. (Taylor & Francis, 2017)
The stable dispersion of nano-additives is highly desirable for the effective lubrication performance of nanolubricants. The compatibility of base oil with selected nano-additives is required for uniform and stable dispersion. This research evaluated the dispersion stability and tribological characteristics of nano-TiO2/SiO2 (average particle size 50 nm) as an additive in a biobased lubricant. The wear protection and friction reducing characteristics of the formulations were evaluated by four-ball extreme pressure tests and piston ring–cylinder liner sliding tests. Surface analysis tools, including scanning electron microscopy, energy-dispersive X-ray spectroscopy, and atomic force microscopy, were used to characterize the worn surfaces. Results showed that the nanolubricants demonstrated appreciable dispersion capability in the absence of a surfactant and an improvement in load-carrying capacity, antiwear behavior, and friction reduction capability.